Reformed Theology: Identity and Ecumenicity - Sebastian Athappilly (Journal of Dharma, 2004)
This book is a collection of the papers of systematic theologians of the Reformed Tradition who took part in the international consultation convened by the Centre of Theological Inquiry at the Internationales Wissenschaftsforum in Heidelberg, Germany, during March 18-22, 1999. It consists of five parts as follows: “Reformed Identity in Historical Continuity and Contextual Awareness” (Part I), “How to Shape Reformed Ecclesiology” (Part II), “Spirit and Covenant: Reformed Pneumatology in Very Different Contexts” (Part III), “Affirming and Questioning Reformed Doctrines in Ecumenical Conversation” (Part IV), and “Ecumenicity and Ethical Profiles of Reformed Theology: Catholicity and Practical Contextuality” (Part V). In addition to the introduction by the two editors, there are 28 articles/papers, each by a different author dealing with the many relevant themes and challenges for Christian theology from the perspective of Reformed Theology. Thus, the book is the combined effort of 30 scholars.